Incidencia de la cooperación, la cohesión y la eficacia colectiva en el rendimiento en equipos de fútbol. - Marcos, F. M. L.; Sanchez-Miguel, P. A.; Sachez-Oliva, D.; Amado Alonso, D.; Garcia-Calvo, T. (Revista Internacional de Ciencias del Deporte, 2011)
The aim of this work was to examine the relationships between sport cooperation, team cohesion, collective efficacy and collective performance. The sample was formed by 235 football players that played in XI group of the Juvenile National League. All participants were male and ranging in age from 15 to 19 years (M = 17.02; SD = .75). Different instruments were used to assess cooperation, cohesion and collective efficacy, and performance was measured through classification. Results revealed a significant and positive relationship between those variables. Finally, we showed a theoretical model that included the different psychological variables used as an instrument to reach greater performance.